When should we obtain images for an older adult with acute vertigo?. Issue 10 (October 2017) - Kalkhoff, Michael; Wipperman, Jennifer
Abstract : EVIDENCE‐BASED ANSWER : For older adults with acute vertigo for more than 24 hours, normal HINTS or HINTS Plus examinations have negative likelihood ratios of 0.04 or less, making them good for ruling out stroke and likely precluding the need for imaging. Patients with positive HINTS or HINTS Plus examinations should undergo imaging. The ABCD2 score has a lower sensitivity and should not be used for ruling out stroke (SOR: A, systematic review of observational studies and 2 additional cross‐sectional studies).